The P-selectin gene polymorphism val168met: a novel risk marker for the occurrence of primary ventricular fibrillation during acute myocardial infarction - Elmas, Elif; Bugert, Peter; Popp, Tatjana; Lang, Siegfried; Weiß, Christel; Behnes, Michael; Borggrefe, Martin; Kälsch, Thorsten (Journal of cardiovascular electrophysiology, 2010)
Aims: Ventricular fibrillation (VF) in the setting of acute myocardial infarction (AMI) is the leading cause of sudden cardiac death (SCD). Family history of SCD is described as risk factor for primary VF during acute AMI. Genetic factors may be associated with primary VF. We examined polymorphisms in genes related to the activation and adhesion of blood platelets in patients with and without VF in the setting of AMI and among healthy controls. Methods: Two hundred and forty patients with a history of AMI and 475 healthy controls were studied. Seventy-three patients (30%) had primary VF during AMI. By using PCR techniques with sequence-specific primers (PCR-SSP), we genotyped 5 single nucleotide polymorphisms (SNPs) in P-selectin (SELP) (V168M, S290N, N592D, V599L, T715P), 2 SNPs (M62I, S273F) in P-selectin glycoprotein ligand-1 (SELPLG), 5 SNPs in CD40LG (−3459A>G, −122A>C, −123A>C, 148T>C, intr4-13T>C), the H558R SNP in SCN5A, and rs2106261 in ZFHX3. In addition, length polymorphisms in SELPLG (36bp-tandem repeat) and CD40LG (CA-repeat) were genotyped by PCR methods. Results were evaluated by 2-sided t-tests, chi-square tests, and logistic regression analysis. Results: None of the gene polymorphisms showed significant differences between AMI patients and healthy controls. Among patients with a history of VF, however, the SELP 168M variant showed a significantly higher prevalence (14/73 patients; 19.2%) as compared with patients without VF (13/167 patients; 7.8%; P < 0.01). This association remained significant in a logistic regression analysis after adjustment for age and gender (P = 0.013; odds ratio 2.8; 95% confidence interval 1.2-6.3). Conclusions: This is the first description of an association of the SELP gene variant 168M with primary VF during acute MI. This variant may be a candidate polymorphism for evaluating the susceptibility for VF in the setting of acute MI.
Gesehen am 22.05.2023